Investigations of Volatile Organic Compounds in Berries of Different Actinidia kolomikta (Rupr. & Maxim.) Maxim. Accessions - Laima Cesoniene; Remigijus Daubaras; Sigita Bogacioviene; Audrius Sigitas Maruska; Mantas Stankevicius; Andrius Valatavicius; Marcin Zych; Sezai Ercisli; Gulce Ilhan (Polish Journal of Food and Nutrition Sciences)
The composition of volatile organic compounds contributes to fruit flavour and is an important element of fruit quality. Berries of sixteen cultivars and female clones of Actinidia kolomikta were studied by GC-MS with headspace solid phase microextraction method. In total, 89 compounds were separated and identified. These compounds were classified as terpenes, esters, alcohols, aldehydes, anhydrides, diazoles, hydrocarbons, and ketones. Among volatile organic compounds, esters were the most abundant. Significant differences in the diversity of volatile organic compounds were found among A. kolomikta cultivars and clones. Based on these results, we selected potential accessions for the breeding of new cultivars. Summarising the results of this study, the accessions of A. kolomikta were grouped according to the main flavour compounds.